Studi Normatif Legalitas Peran Tokoh Masyarakat Dalam Undang-Undang No. 7 Tahun 2012 Tentang Penanganan Konflik Sosial - Rayno Dwi Adityo (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2017)
Currently indonesia often torn asunder with different kinds of events which is quite disturbing national stability start of the disintegration by separatist group and other’s. It is something that can be easy occur given indonesia is a archipelago state, so in controlled requires strength tight from own society or the state of directly. With the diversity of social conflict tribal often law ineffective so that we consider that the need for the role of an instrument informal as community figures, traditional leaders and religion figures that more actively in acktivity has purpose for making stability the condition from social conflict. This research, writter trying to give some description that is the participation from community, traditional leaders and religion figures most important for resolving the conflict and as the law in Indonesian that participation this fegures had tranformation from unformal side to formal side as the UU No. 7 Tahun 2012 Tentang Penanganan Konflik Sosial mandating. Key Words: Law, to respon, community figures, formal and unformal.